2007
DOI: 10.1021/bm060921n
|View full text |Cite
|
Sign up to set email alerts
|

Radiopaque Organic−Inorganic Hybrids Based on Poly(d,l-lactide)

Abstract: Hybrid organic-inorganic nanocomposites were prepared starting from alpha,omega-triethoxysilane-terminated poly(d,l-lactic acid) (PDLLA) to be used as potential radiopaque biocompatible coatings for medical devices. The synthesis of the organic phase precursors of given chain length was achieved via anionic polymerization of d,l-lactide using a bifunctional initiator and subsequent triethoxysilane functionalization of the end groups. PDLLA-based ceramers (ceramic polymers) were then synthesized by the sol-gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…27 Good radiopacity of organic-inorganic hybrids has been recently reported, suggesting that these materials might find applications in medical fields where X-ray visibility is required. 28,29 Because radiopacity is associated with the presence of the inorganic component, the latter content must be quite high for thin hybrid coatings to reach a good level of radiopacity. As a consequence, the coating layer tends to be rigid and to form cracks upon deformation.…”
Section: Introductionmentioning
confidence: 99%
“…27 Good radiopacity of organic-inorganic hybrids has been recently reported, suggesting that these materials might find applications in medical fields where X-ray visibility is required. 28,29 Because radiopacity is associated with the presence of the inorganic component, the latter content must be quite high for thin hybrid coatings to reach a good level of radiopacity. As a consequence, the coating layer tends to be rigid and to form cracks upon deformation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Hyb‐75, for which the highest number of TiOC covalent bonds was revealed by FT‐IR measurements (Figure 3), the interaction between the phases is so strong that almost no glass transition is detected, despite the fact that in this hybrid the amount of polymer is more than 50 wt.‐%. For Class II hybrids it was previously reported that the glass transition temperature of polymers whose chain ends are locked into the inorganic network increases upon hybrid synthesis 60–63. However the T g values reported in Table 3 show an opposite trend, with the T g in the hybrid samples being lower than in the PTMC polymer precursor.…”
Section: Resultsmentioning
confidence: 83%
“…In the first case, fibers were collected at a slow rotation of the drum (about 60 rpm), in the latter a speed of 2,500 rpm was applied to guarantee a prevailing alignment. Nanofibrous mats were finally washed with distilled water and dried at 70 C in order to remove LiCl salt residue, as previously reported [22,23]; thickness of washed fibers membranes decreases down to about 50 μm.…”
Section: Nanofibrous Mats Productionmentioning
confidence: 99%
“…PMIA can be solubilized in the presence of inorganic salts (LiCl) and can be easily processed to produce nanofibrous membranes. The production of nanofibers via electrospinning starting from PMIA solution has been already approached and optimized [23], and nanofibers can be obtained with a significantly different extent of orientation both by playing on the processing and environmental parameters [18] or, as in the present case, by simply varying the rotation speed of the rotating drum used for accumulating and recovering the nanofibers. The difference in the fibers alignment could significantly modify the fire response of the final material, when used as outer coating: indeed, membranes based on randomly oriented fibers would guarantee a isotropic behavior to the coating layer, while the aligned ones are far better behaving in a single direction, while the cross-sectional behavior might suffer from the poor cohesion of the fibers.…”
Section: Nanofibrous Membranes Production and Characterizationmentioning
confidence: 99%